2020
DOI: 10.1155/2020/8861358
|View full text |Cite
|
Sign up to set email alerts
|

Responsive Expression of MafF to β-Amyloid-Induced Oxidative Stress

Abstract: The small musculoaponeurotic fibrosarcoma (sMaf) proteins MafF, MafG, and MafK are basic region leucine zipper- (bZIP-) type transcription factors and display tissue- or stimulus-specific expression patterns. As the oxidative stress reactive proteins, sMafs are implicated in various neurological disorders. In the present study, the expressions of sMafs were investigated across five databases gathering transcriptomic data from 74 Alzheimer’s disease (AD) patients and 66 controls in the Gene Expression Omnibus (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 51 publications
(21 reference statements)
1
13
0
Order By: Relevance
“…ZCY020, a Lathyrol derivative with abundant amount and considerable activity, was chosen for further mechanism studies both in vitro and in vivo. Consistent with previous studies [28][29][30], our data suggested that LPS markedly increases MAFF expression, whereas ZCY020 reverses this effect and keeps it at a certain level. At the same time, the expression and the level of nuclear translocation of Nrf2 were increased by ZCY020, and these changes went on to facilitate the formation of the MAFF-Nrf2 heterodimer.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…ZCY020, a Lathyrol derivative with abundant amount and considerable activity, was chosen for further mechanism studies both in vitro and in vivo. Consistent with previous studies [28][29][30], our data suggested that LPS markedly increases MAFF expression, whereas ZCY020 reverses this effect and keeps it at a certain level. At the same time, the expression and the level of nuclear translocation of Nrf2 were increased by ZCY020, and these changes went on to facilitate the formation of the MAFF-Nrf2 heterodimer.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, the role of sMafs in transcriptional activation or repression is highly dependent on their quantity and the abundance of their binding partners. An increasing number of researches have proved that the transcription and protein levels of MAFF are induced by inflammatory cytokines such as IL-1β and TNF [28,29], and also by oxidative stress [30], indicating the specific role for MAFF in the cases of oxidative stress and inflammation. Recent research has also reported that under LPS stimulation, MAFF acts as a pro-inflammatory transcription factor [31].…”
Section: Introductionmentioning
confidence: 99%
“…The aberrant STC2 expression has significant consequences for the prediction, incidence, metastasis, and prognosis of different cancers, including various cancers of the liver, colon, and prostate [29]. MAFF is a part of the essential leucine zipper (bZIP) transcription factor Maf family and plays a key role in numerous physiological and pathological processes, including signal transduction, hematopoiesis, central nervous system activity, and tumorigenesis [30,31]. With the fourgene signatures, it was seen that this was an independent factor that affects the prognosis of osteosarcoma and that the model had a stronger effect in forecasting osteosarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…NRF1 and NRF3 also bind to AREs but are relatively understudied [ 42 , 43 ]. Other transcription factors can activate genes with AREs, including EP300 and CREB [ 44 , 45 ], and the sMAF family of proteins (MAFa MAFf and MAFk MAFg), which can homodimerize or heterodimerize with other sMAF members, or the NRF family, to both activate and repress gene expression [ 46 , 47 ]. Repressors of NRFs include the BTB domain and CNC homologs 1 and 2 (BACH1 and BACH2), which can form heterodimers with members of the MAF and NRF families, thereby preventing the overactivation of antioxidant pathways [ 46 ].…”
Section: Oxidative Stress In Health and Diseasementioning
confidence: 99%